Indonesia's strategies for joining the ASEAN digital economy framework agreement - Hasran; Karima Taushia (Center for Indonesian Policy Studies (CIPS), 2024)
This policy brief presents the possible contents of DEFA by mapping relevant elements of the digital economy from existing agreements. The mapping indicates areas with extensive coverage by existing regional arrangements (cross-border paperless trade, cyber security, e-commerce, digital payment, digital ID, and personal data protection) and areas and issues that are less regulated by regional arrangements (digital inclusivity, emerging technology, and climate). Indonesia should map out areas of strength and weakness in domestic regulation and system interoperability on the possible content of DEFA. For the areas of strength, where domestic laws and system interoperability exist, or joint commitments and initiatives for harmonization within the region are underway, the directorate should push for strong cooperation and binding commitments in the agreement. Meanwhile, a more moderate approach should be proposed for less developed areas regarding regulatory frameworks and interoperability.
Keywords: 330